PWE-067 Can serum nutritional markers be used for diagnosing pancreatic exocrine insufficiency in at risk groups?. (June 2019) - Jalal, M; Campbell, JA; Hopper, AD
Abstract : Introduction: Patients with pancreatic exocrine insufficiency (PEI) are at an increased risk of nutritional deficiency which can lead to cardiovascular disease and associated mortality. Faecal elastase-1 (FEL-1) has a good sensitivity and specificity in severe PEI but the diagnostic accuracy decreases in mild to moderate PEI. Some serum nutritional markers and vitamin serum levels have been shown to be associated with malnutrition. The aim of this study was to investigate if serum nutritional markers could be used to diagnose PEI. Methods: Patient at high risk of PEI (abdominal pain suggestive of chronic pancreatitis, high alcohol intake and diabetes mellitus) were prospectively recruited. Patients with known PEI or taking enzyme replacement therapy were excluded. All patients had demographic information collected, BMI calculated and FEL-1 performed. Blood samples were taken for levels of sodium, potassium, calcium, magnesium, phosphate, prealbumin, vitamin D, copper, zinc and selenium. A FEL-1 result of <200 µg/g was considered as indicating PEI which was confirmed on repeat testing and investigated further. Results: A total of 144 patients were included in the study (mean age 52.1 ± 18 years, 76 males). A FEL-1 <200 was detected in 46 patients 46/144 (32%) indicating presence of PEI. There was no significant difference between PEI and non-PEI groups in age (54.8 vs 50.8 years, p=0.11) or BMI (27.8 vs 27.9 kg/m 2, p = 0.91). A significant number of PEI patients had selenium deficiency 8/31 (25.8% below normal level) compared to non-PEI group 7/98 (7.4%), p= 0.028. None of the patients with normal pancreatic function and morphology on images had low selenium (0/30) compared to patients with PEI and confirmed chronic pancreatic changes 5/17 (29.4%), p = 0.004. Analyses of other markers did not show significant differences in proportions of biochemical marker deficiencies between PEI and non-PEI groups. Using selenium (<0.61 µmol/l) as a marker of PEI in high risk groups gave a sensitivity, specificity, positive predictive value and negative predictive value of 25.81% (95% CI=12.3%-38.5%), 92.45% (95% CI=83%-98%), 66.66% (95% CI=39.3%-86%), 68.06% (95% CI=58.9%-67%), respectively. Conclusion: Although a selenium deficiency was significantly associated with PEI, its poor sensitivity as a test for PEI would only make it supportive of a diagnosis and other tests would be required. Apart from selenium levels it would appear that checking serum nutritional markers for suspected cases of PEI at diagnosis results in a low diagnostic yield. PEI patients are overweight suggesting that using a low BMI to target patients is insufficient to prompt testing for PEI or malnutrition in this patient group.